Analisis Yuridis Peristiwa Pagar Laut Ditinjau Dari Hukum Nasional Dan Hukum Laut Internasional - Dendi Saputra; Deyan Ajian Putra; Indah Salsabilla Putri; Ema Septaria; M. Ilham Adepio (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The sea fence phenomenon at Pantai Indah Kapuk 2 (PIK 2) raises legal issues related to reducing community access and adverse impacts on the environment. This research aims to conduct a further study of legal violations arising from the sea fence incident. This research was conducted by analyzing and systematizing the data and information obtained qualitatively. Data on legal violations due to the sea fence phenomenon were collected using the literature study method. The data collected was analyzed using normative legal methods with a statutory and conceptual approach. The results of this study inform that the phenomenon of sea fencing violates various provisions of Indonesian laws and regulations. Furthermore, the sea fencing phenomenon is also identified as contradicting the principles of sustainable marine resource management and potentially violating the state’s obligation to protect and preserve the environment as per Article 192 of UNCLOS 1982.